UML is Back. Or is it? Investigating the Past, Present, and Future of UML in Open Source Software - Romeo, Joseph; Raglianti, Marco; Nagy, Csaba; Lanza, Michele (Proceedings / International Conference on Software Engineering, 2025)
Since its inception, UML, the Unified Modeling Language, has been touted as the way to go when it comes to designing and documenting software systems. While being an integral part of many university software engineering programs, UML has found little consideration among developers, especially in open source software. Reasons for this include that UML shares some shortcomings with other forms of documentation (e.g., limited availability, outdatedness, inadequate level of detail). We present a study to investigate the evolution and the current situation regarding the use of UML in open source projects. We mined and analyzed ~ 13k GitHub projects, developing strategies and heuristics to identify UML files through their extensions and contents, for a quantitative analysis of two decades of evolution of the usage of UML. We explored the popularity of UML, derived characteristics of projects leveraging UML, and analyzed the authors, creators and maintainers, of UML artifacts. Our study confirms that UML is indeed still under-utilized. At the same time we found evidence of a resurgence coinciding with the popularity of human-readable text-based formats, defined and used by tools like PlantUML and Mermaid. We discuss how identifying and addressing the new challenges implied by this resurgence could impact the future of UML.